From Morality to Psychology: Concepts of Emotion in Urdu, 1870-1920 - Pernau, Margrit (2025)
This article looks at the changes in the concepts used to write about emotions in Urdu between 1870 and 1920. It argues that while emotions at the beginning of the period were still thought of as premised upon notions of equilibrium and balance, which accorded a crucial role to the will and to rationality, fifty years later concepts celebrated the elementary power of emotions and their capacity to overwhelm the individual. This can be read as an indicator and factor of a profound emotionalization of private as well as public life. The first section looks at ethical and pedagogical texts, the second at articles published in journals linked to the reformist Mohammedan Anglo-Oriental College at Aligarh, and the final section at the reconfiguration of emotion knowledge through the translation and adaptation of psychological treatises.